Role of pre‐transplant chest high‐resolution computed tomography and serum galactomannan index in predicting post‐transplant invasive pulmonary aspergillosis in allogeneic hematopoietic cell transplant recipients. Issue 4 (22nd May 2021) - Sharma, Rintu; Singh, Charanpreet; Khadwal, Alka; Prakash, Gaurav; Malhotra, Pankaj; Jain, Arihant; Jandial, Aditya; Suri, Vikas; Muthu, Valliappan; Prabhakar, Nidhi; Gorsi, Ujjwal; Chakrabarti, Arunaloke; et al.
Abstract: Introduction: The role of pre‐HCT chest high‐resolution computed tomography (HRCT) and serum galactomannan index (GMI) in predicting the post‐allogeneic hematopoietic cell transplant (HCT) invasive pulmonary aspergillosis (IPA) is debatable. Methods: This was a single‐center, prospective study from 2014 to 2019. The primary objective was to study if pre‐HCT chest HRCT and serum GMI predicted IPA post‐HCT. The secondary objective was day +100 mortality. All consecutive, consenting patients of ≥12 years of age undergoing allo‐HCT were included and had pre‐HCT chest HRCT and serum GMI. All patients received mold active antifungal prophylaxis. The EORTC/MSG criteria were used for the diagnosis of IPA. Results: A total of 82 patients with median age 27 years (12‐59 years) were included. The underlying diagnoses included hematological malignancies (79%) and aplastic anemia (21%). Fifteen percent of patients was treated for prior history of probable IPA (>6 weeks before HCT). Pre‐HCT chest HRCT satisfied EORTC clinical criteria in 24% patients. Serum GMI ≥0.5 was seen in 27% of patients. Post‐HCT probable IPA was seen in 24% of patients. There were more patients with pre‐HCT chest HRCT findings satisfying EORTC clinical criteria (45% vs. 18%, P  = .014) and GMI ≥0.5 (45% vs. 21%, P  = .03) in the group with post‐HCT IPA compared to those without IPA. There was higher day+100 mortality in patients with post‐HCT IPA (55% vs. 18%, P  = .001). Conclusions: The presence of EORTC clinical criteria on pre‐HCT chest HRCT, serum GMI ≥0.5, and prior history of IPA predicted post‐HCT IPA.